Refractoriness in Tsetse Flies (Diptera: Glossinidae) May be a Matter of Timing. Issue 4 (28th October 2014) - Nayduch, Dana; Aksoy, Serap
Abstract : Tsetse flies (Diptera: Glossinidae: Glossina spp.) are vectors for African trypanosomiasis, a devastating disease that kills both people and animals in sub-Saharan Africa. Trypanosomes ingested with an infected bloodmeal reside within the gut of tsetse and eventually move to the salivary glands where they become transmissible during blood feeding. Although tsetses are efficient vectors for disease transmission, infection prevalence in the field is surprisingly low, a trait referred to as refractoriness. Refractoriness is relatively more pronounced in palpalis subgroup flies, although certain species within the susceptible morsitans species complex are also highly refractory, such as Glossina pallidipes Austen. We examined the role of the humoral immune response in refractoriness to infection by comparing the expression of the antimicrobial peptide gene attacin across three species with varied vector competence. Gene expression was measured both temporally (time after feeding and fly age) and spatially (tissue specificity). Although microbial immune challenge induces attacin expression in all three species, "refractory" fly species showed an uninduced, baseline level of systemic (fat body) attacin, whereas the "susceptible" flies did not. In addition, refractory species had a higher level of attacin expression in the proventriculus and midgut. We also found that blood feeding alone up-regulated attacin expression in refractory species but not in the susceptible species. Finally, reverse genetics showed that repression of attacin by double-stranded RNA-mediated RNA interference increased susceptibility to trypanosome infection in G . pallidipes . The role of early, uninduced attacin expression, and its role in relative refractoriness in tsetse, is discussed.